Antibiotic use and bacterial complications following upper respiratory tract infections: a population-based study. Issue 11 (15th November 2017) - Cars, Thomas; Eriksson, Irene; Granath, Anna; Wettermark, Björn; Hellman, Jenny; Norman, Christer; Ternhag, Anders
Abstract : Objectives: To investigate if use of antibiotics was associated with bacterial complications following upper respiratory tract infections (URTIs). Design: Ecological time-trend analysis and a prospective cohort study. Setting: Primary, outpatient specialist and inpatient care in Stockholm County, Sweden. All analyses were based on administrative healthcare data on consultations, diagnoses and dispensed antibiotics from January 2006 to January 2016. Main outcome measures: Ecological time-trend analysis : 10-year trend analyses of the incidence of URTIs, bacterial infections/complications and respiratory antibiotic use. Prospective cohort study : Incidence of bacterial complications following URTIs in antibiotic-exposed and non-exposed patients. Results: The utilisation of respiratory tract antibiotics decreased by 22% from 2006 to 2015, but no increased trend for mastoiditis (p=0.0933), peritonsillar abscess (p=0.0544), invasive group A streptococcal disease (p=0.3991), orbital abscess (p=0.9637), extradural and subdural abscesses (p=0.4790) and pansinusitis (p=0.3971) was observed. For meningitis and acute ethmoidal sinusitis, a decrease in the numbers of infections from 2006 to 2015 was observed (p=0.0038 and p=0.0003, respectively), and for retropharyngeal and parapharyngeal abscesses, an increase was observed (p=0.0214). Bacterial complications following URTIs were uncommon in both antibiotic-exposed (less than 1.5 per 10 000 episodes) and non-exposed patients (less than 1.3 per 10 000 episodes) with the exception of peritonsillar abscess after tonsillitis (risk per 10 000 tonsillitis episodes: 32.4 and 41.1 in patients with no antibiotic treatment and patients treated with antibiotics, respectively). Conclusions: Bacterial complications following URTIs are rare, and antibiotics may lack protective effect in preventing bacterial complications. Analyses of routinely collected administrative healthcare data can provide valuable information on the number of URTIs, antibiotic use and bacterial complications to patients, prescribers and policy-makers.